Modeling the change in groundwater level under constant water supply (MMIT Proceedings, 2025)
This article presents a model designed to determine changes in groundwater levels. The model is intended for the scientific substantiation of the intensity of water-melioration processes in agricultural lands, the optimization of drainage system calculations, and the improvement of irrigation regime management. It schematically illustrates two main kinetic processes resulting from the interaction between groundwater and the external environment — groundwater flow and processes occurring in the dried-up zone. The schematization of groundwater interaction with the reservoir demonstrates the achievement of water balance. Methods and examples for determining the parameters of groundwater level modeling are provided, and the consistency between calculation results and experimental data serves as sufficient justification for the model’s practical application